SURVIVAL AND GROWTH OF CULTIVATED FISHES IN ASSAM PONDS - Lakshmanan, M A V; Bhuyan, B R; Radhakrishnan, S; Babu, N (Indian Journal of Fisheries, 2011)
INFORMATION on the natural survival and growth of fishes is a basic necessityto consider improvement measures in fish culture. In India, however, suchuseful information on a regional basis is at present very limited and inadequate.It is a well-known fact that the productivity of fish in natural waters is dependenton a wide variety of physical, chemical and biological conditions of thewater. Hence, it is essential to make a thorough study of these water conditionsunder which fish are cultured, in order to elucidate the causative factors involvedand control survival and growth. Though such a detailed study for a vast regionhas its own limitations, an attempt was made by the Pond Culture Research Unitof the Central Inland Fisheries Research Institute at Joysagar, to gather theessential basic data, viz., data on natural survival, growth and production of thethree species in normally prepared typical fish ponds of Assam, without fertilisationand supplementary feeding of fish.This paper embodies the results of investigations carried out during theperiod 1960 to 1963.